INTERPRETATION, ETHICS, AND THE COMPLEX RELATIONSHIP BETWEEN A PROPHET AND AN ??????? ????????? - C J Redelinghuys (Acta Theologica)
The ontological turn in hermeneutics made it increasingly clear that an interpreter’s “inner self” is not detached from the world in which s/he lives. This had a profound impact on not only how one conceives of the process of interpretation, in general, but also how one thinks of ethical evaluation and appropriation, in particular. In this regard, the narrative of Hosea’s marriage to Gomer (Hos. 1-3) presents an interesting test case for how an interpreter’s previously established moral framework influences his/her current understanding of the biblical text. To illuminate this matter, three prominent ethical theories (consequentialism, deontology, and virtue ethics) are used as interpretative frameworks. Finally, the author reiterates that pre-understanding plays an important role in biblical interpretation. This matter is often more complex than simply focussing on theological presuppositions in terms of dealing with different ethical questions and challenges.